Correlation Analysis of Hypothalamic-Pituitary-Adrenal Axis Hormone Levels in Hair before Stroke Onset and Mood Disorders after Stroke - WANG Tiantian; JIA Yuanyuan; QI Deyi; DENG Huihua; MENG Dianhuai (康复学报)
ObjectiveTo explore the expression of hypothalamic-pituitary-adrenal (HPA) axis related hormones such as cortisol (F), cortisone (E) and dehydroepiandrosterone (DHEA) in hair before the onset of stroke and their correlation with post-stroke mood disorders.MethodsA total of 62 patients with stroke were recruited in the Jiangsu Province Hospital, the Second Affiliated Hospital of Nanjing Medical University and Nanjing Qixia District Hospital from November 2022 to May 2023. According to the survey results of Hamilton depression scale-24 (HAMD-24) and Hamilton anxiety scale-14 (HAMA-14), the patients were divided into post-stroke depression group, post-stroke non-depression group, post-stroke anxiety group and post-stroke non-anxiety group. Another 40 healthy subjects matched for age, sex and body mass index were included as the healthy control group. The levels of F, E and DHEA in hair before onset were compared, and the correlation between these three hormone levels and HAMD-24 and HAMA-14 scores were analyzed.ResultsThe level of F in hair before stroke onset was significantly higher in the post-stroke depression group than that in the post-stroke non-depression group and healthy control group (P<0.05), and the level of E in post-stroke depression group was significantly higher than that in the healthy control group (P<0.05). The levels of F and E in hair before onset were significantly higher in the post-stroke anxiety group than those in the post-stroke non-anxiety group and the healthy control group (P<0.05). There was no significant difference in DHEA levels between stroke patients group and healthy control group (P>0.05). The levels of F and E in hair of stroke patients before onset were positively correlated with HAMD-24 and HAMA-14 scores (P<0.05). ROC analysis indicated that the cut-off value of F in hair for the diagnosis of post-stroke depression was 24.35 pg/mg, with an AUC of 0.725 (0.594, 0.856), a sensitivity of 73.70%, and a specificity of 73.50%. The cut-off value of E in hair for the diagnosis of post-stroke depression was 49.65 pg/mg, with an AUC of 0.734 (0.595, 0.874), a sensitivity of 73.70%, and a specificity of 78.30%. The cut-off value of F in hair for the diagnosis of post-stroke anxiety was 36.60 pg/mg, with an AUC of 0.803 (0.702, 0.904), a sensitivity of 68.80%, and a specificity of 82.60%. The cut-off value of E in hair for the diagnosis of post-stroke anxiety was 57.50 pg/mg, with an AUC of 0.815 (0.689, 0.940), a sensitivity of 81.30%, and a specificity of 81.40%.ConclusionThe levels of F and E in hair of patients with post-stroke depression or anxiety significantly increase before onset and are significantly positively correlated with HAMD-24 and HAMA-14 scores, both of which could be used as potential predictors of post-stroke mood disorders.